Studi Naratif Persepsi Orang Tua Terhadap Implementasi Pembelajaran Daring Bagi Anak Gangguan Spektrum Autisme di Smk Negeri 7 Padang - Hanum, Taskia; Rahmahtrisilvia, Rahmahtrisilvia (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the implementation of online learning for GSA children. Learning that is usually carried out face-to-face has been turned into online learning. GSA children find it difficult to understand online learning without parental assistance. This study aims to determine the parents' perception of the implementation of online learning for children with GSA. The research method is a qualitative narrative study, the subjects in the study are the parents of GSA children. Data were collected through interviews and documentation studies. Wet data technique through triangulation, using reference materials and checking. The results showed that parents' perceptions of the implementation of online learning were in parents' perceptions of the preparation stage, implementation stage, evaluation stage and constraints. Preparation of parents is to prepare infrastructure and facilities. Parents' perceptions of the implementation stage are accompanying children from the start of learning to completion of learning. Parents' perception of the evaluation stage is that the teacher gives assignments in writing and orally. Parents' perceptions of the constraints are personal constraints, technical constraints, implementation constraints and financial constraints.